Kidney Disease-Specific Quality of Life among Patients on Hemodialysis - Issa Al Salmi; Pramod Kamble; Eilean Rathinasamy Lazarus; Melba Sheila D’Souza; Yaqoob Al Maimani; Suad Hannawi (International Journal of Nephrology, 2021)
Introduction. Quality of life (QoL) of hemodialysis patients can be examined in two aspects: kidney-specific quality of life and general quality of life. Objective. To determine the QoL among patients undergoing hemodialysis, to assess patients’ QoL on hemodialysis, and to determine the factors associated with QoL among hemodialysis patients in Oman. Method. A cross-sectional study was carried out with 205 patients to measure the QoL across various demographic and clinical variables in Oman. The Arabic version of the KDQOL-SFtool was used to collect data from patients undergoing hemodialysis to give QoL quantitative measures. Results. The physical-QoL was 45.7 (95% CI, 44.3, 47.0), which is less than half that of a healthy human. The emotional-QoL is 53.33 (95% CI, 51.1, 55.5), slightly more than half in a healthy human-QoL. The difference between physical and emotional-QoL scores is −7.66 (95% CI, −10.3, -5.1), showing that physical QoL is significantly less than emotional-QoL. The overall general QoL score was 49.5 (95% CI, 47.8, 51.2), half the QoL score of a healthy human. Younger patients are also more likely to experience emotional problems compared with older patients. Patients with 5–8 mg/l levels of serum creatinine have lower emotional wellbeing. People on low incomes experienced social difficulties, while the maximum burden was found in physical activities and minimum social function. Conclusion. Both physical (45.7) and emotional (53.3) QoL scores in dialysis patients are nearly half those of an average human. Hence, there is a poor QoL among dialysis patients like other studies, and therefore, further improvement of renal rehabilitation in dialysis patients is warranted to improve patients’ QoL.